Across the stages: a multiscale extension of the generalized stochastic microdosimetric model (MS-GSM2) to include the ultra-high dose rate - Battestini, Marco; Missiaggia, Marta; Attili, Andrea; Tommasino, Francesco; La Tessa, Chiara; Cordoni, Francesco G.; Scifoni, Emanuele (Frontiers in Physics, 2023)
Ultra-high dose rate (UHDR) irradiations with different types of radiation have shown a larger sparing of normal tissue and unchanged tumor control with respect to conventional delivery. In recent years, there has been an accumulation of experimental evidence related to the so-called FLASH effect. However, the underpinning mechanism remains, to date, extremely debated and largely unexplained, while the involvement of multiple scales of radiation damage has been suggested. Since it is believed that the chemical environment plays a crucial role in the FLASH effect, this work aims to develop a multi-stage tool, the multiscale generalized stochastic microdosimetric model (MS-GSM2), that can capture several possible effects on DNA damage at the UHDR regime, such as reduction of DNA damage yield due to organic radical recombination, damage fixation due to oxygenation, and spatial and temporal dose deposition effects, allowing us to explore most of the candidate mechanisms for explaining the FLASH effect. The generalized stochastic microdosimetric model (GSM2) is a probabilistic model that describes the time evolution of DNA damage in a cell nucleus using microdosimetric principles, accounting for different levels of spatio-temporal stochasticity. In particular, the GSM2 describes radiation-induced DNA damage formation and kinetic repair in the case of protracted irradiation without considering the Poissonian assumption to treat the number of radiation-induced DNA damage. In this work, we extend the GSM2, coupling the evolution of DNA damage to fast chemical reaction kinetics, described by a system of ordinary differential equations, accounting for an additional level of stochasticity, i.e., in chemistry. We simulate energy deposition by particles in a microscopic volume, which mimics the cell nucleus, in order to examine the combined effects of several chemical species and the time evolution of DNA damage. We assume that UHDR modifies the time evolution of the peroxyl radical concentration, with a consequent reduction in the yield of the indirect DNA damage. This damage reduction emerges only at UHDR and is more pronounced at high doses. Moreover, the indirect damage yield reduction depends on the radiation quality. We show that the MS-GSM2 can describe the empirical trend of dose- and dose rate-dependent cell sensitivity over a broad range, particularly the larger sparing of healthy tissue occurring at the FLASH regime. The complete generality of the MS-GSM2 also allows us to study the impact of different dose delivery time structures and radiation qualities, including high LET beams.